PENGARUH PENGETAHUAN KEUANGAN DAN LITERASI KEUANGAN TERHADAP PERILAKU KEUANGAN MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS RIAU - Reska Nada Putri; Gusnardi Gusnardi; Mujiono Mujiono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of financial knowledge and financial literacy on the behavior of students of the University of Riau's economic education. The population in this study were all economic education students in the accounting and cooperative majors in 2015 and 2016, namely 164 students and in this study the sampling used was probability sampling with purposive sampling sampling technique with a total of 89 students. To determine the number of samples using criteria, namely all students of 2015 and 2016 Economic Education and students who do not take accounting concentration. Data collection techniques used were questionnaires and tests, tests of students' financial knowledge and questionnaires about financial literacy and student financial behavior that was distributed to respondents. Data analysis using descriptive analysis, and multiple linear regression analysis, the results of this study conclude that financial knowledge and financial literacy affect the financial behavior of students of Economic Education.Key Words: Financial Knowledge, Financial Literacy And Financial Behavior